The Correlation Between Undergraduate-Students’ Reading Interest and Their Reading Comprehension - Dewi Fatima Nur Alfatihah; Peptia Asrining Tyas (Journal of Languages and Language Teaching, 2022)
Reading interest is one aspect of encouraging the reading comprehension process. However, the level of reading interest in Indonesia is still low. In this situation, as an academic component, undergraduate-students also have an obligation to read. This is driven by the academic life of lectures which require students to have reading comprehension skills. Because of these two circumstances, the reason for this study was to investigatethe correlation of students' reading interest and reading comprehension in higher education levels. This study was conducted through a quantitative approach and correlation study as the method. The population of this research is about 140 students of EFL semester four who are active in the English language education study program of Universitas Brawijaya. By using a simple random sampling technique, there were 41 students from the 4th semester involved as participants in this research. This study was conducted by distributing questionnaires to students who were respondents and reading comprehension tests, after which they were input and analyzed through the SPSS program. The finding of this study showed that the significant value was .022 smaller than 0.05 (.022 < 0.05) which means that there was a correlation between interest and reading comprehension, with a Pearson product moment (r-value) of .356, which indicates a weak positive correlation. Therefore, it can be concluded that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It means that there is a significant correlation between reading interest and reading comprehension.